Amblyomma aureolatum (Acari: Ixodidae): new records in Buenos Aires and Santa Fe province, Argentina (FAVE Sección Ciencias Veterinarias, 2016)
In July of 2015 and January of 2016, ticks were recovered from a Geoffroy’s cat (Leopardus geoffroyi) in Buenos Aires province and from a domestic dog (Canis lupus familiaris) in Santa Fe province, respectively. All ticks were identified as Amblyomma aureolatum. This report is the first record of A. aureolatum in Buenos Aires province and the first record in domestic dogs of Santa Fe province. Amblyomma aureolatum is a recognized vector of Rickettsia rickettsii, a spotted fever group agent in humans, and of Rangelia vitalii, a pathogenic piroplasmid of dogs, commonly referred to as “nambiuvú”. These findings allow local people to be aware of the presence of A. aureolatum to prevent infestations in dogs, and thus avoiding the occurrence of tick-borne diseases.
Keywords: Amblyomma aureolatum; domestic dog; Leopardus geoffroyi; Santa Fe; Buenos Aires; Argentina